Factors Influencing the Tendency to Subscribe with Takaful Among Martial Arts Practitioners - Siti Hajar Salwa, Ahmad Musadik (2011)
The main purpose of this study is to reveal the factors influencing the tendency to subscribe Takaful among martial arts practitioners. Specifically, three objectives established to compare the different in tendency to subscribe Takaful within demographic factors (age, gender, marital status, income, as well as education level). Beside that, this study also tried to clarify the relationship between four factors of knowledge, awareness, performance of Takaful operators, as well as Islamic religious belief with the tendency to subscribe Takaful and sought to determine whether that four factors of knowledge, awareness, performance of operators, as well as Islamic religious belief have a influence or not with the tendency to subscribe Takaful among martial arts practitioners. The study was conducted among 123 martial arts practitioners in Universiti Utara Malaysia (UUM). The finding of this study suggest that there are have significant different between gender, male and female with the tendency to subscribe Takaful, but in term of age, marital status, income, and education level there are no significant difference with the tendency to subscribe Takaful. Findings also reveal that there are have relationship between factors awareness and no relationship between factors of knowledge, performance of Takaful operator, and Islamic religious belief with the tendency to subscribe Takaful. Finally, the finding also found out that factor of performance of Takaful operator has significant influence with the tendency to subscribe Takaful and the rest did not have significant influence with it. As a conclusion, finding of this study clearly demonstrated that factor of awareness and performance of Takaful operator is the foremost factors that have relationship and influence with respect to tendency to subscribe Takaful.